Analisis Profitabilitas Usahatani Padi (Oryza sativa L) di Kecamatan Pucakwangi Kabupaten Pati - Fatmah, Nur Maulinda; Setiadi, Agus; Ekowati, Titik (Universitas Galuh, 2025)
This research aimed (1) to analyze the income of rice farmers in Pucakwangi District, Pati Regency, (2) to analyze the profitability of rice farming in Pucakwangi District, Pati Regency, and (3) to analyze the influence of land cost factors, labor wages, seed prices, fertilizer prices, pesticide prices, production quantities, and selling prices on the income gained by farmers in Pucakwangi District, Pati Regency. This research was held in May – June 2024 in Pucakwangi District, Pati Regency. The selection of research locations was based on data from Badan Pusat Statistik (2023) which showed that Pucakwangi District is the second largest rice producer among districts in Pati Regency. The research method used was a survey method with a sample size of 100 farmers. Data collection was carried out by distributing questionnaires to be filled in by respondent farmers and by conducting direct interviews. The data analysis methods used include income analysis, profitability analysis, and multiple linear regression analysis. The research results showed; (1) the average production costs incurred by rice ,farmers was equal to IDR2.963.631/0,28 ha/MT or IDR10.691.023/ha/MT, (2) the average revenue obtained by rice farmers was equal to IDR12.105.214/0,28 ha/MT or IDR44.050.314/ha/MT, (3) the average net income obtained by rice farmers was equal to IDR9.141.583/0,28 ha/MT or IDR33.359.291/ha/MT, (4) the average profitability of rice farming was equal to 308% (5) there were significant differences between the income of rice farmers and the MSEs of Pati Regency, (6) there were a significant difference between the profitability of rice farming and the BRI credit interest rate, (7) land costs, labor wages, seed costs, fertilizer costs, pesticide costs, selling prices, and the amount of production simultaneously influenced farmers' income, and (8) land costs, fertilizer costs, production quantities, and selling prices partially significally influenced farmers' income, and (9) labor wages, seed cost, and pesticide costs partially did not significally influence farmers’ income.